1997
DOI: 10.1111/j.1559-1816.1997.tb01648.x
|View full text |Cite
|
Sign up to set email alerts
|

To Picture or Not to Picture: Levels of Erotophobia and Breast Self‐Examination Brochure Techniques1

Abstract: People's level of erotophobia influences their acceptance of sexually related situations, including the likelihood of engaging in sexually related health care such as breast selfexaminations (BSE). Female college students (n = 61) completed a measure of erotophobia and read a BSE brochure that either did or did not contain instructional photographs showing a woman's breasts. As hypothesized when the brochure contained photographs, women high in erotophobia felt less competent in giving themselves BSE and were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…An erotophilic person is more likely to engage in diverse facets of sexuality (Lanciano et al, 2016;Rye, Serafini & Bramberger, 2015), to think about sex more often, to masturbate and fantasize more frequently, and have more intercourse partners than erotophobic individuals (Fisher et al, 1988b). Erotophilic people are also more likely to engage in sex-related health care and to use contraception (Fisher et al, 1988b;Herbenick, Reece, & Hollub, 2009;Labranche, Helweg-Larsen, Byrd, & Choquette, 1997;Rudolph, 2016).…”
Section: Erotophobia-erotophiliamentioning
confidence: 99%
“…An erotophilic person is more likely to engage in diverse facets of sexuality (Lanciano et al, 2016;Rye, Serafini & Bramberger, 2015), to think about sex more often, to masturbate and fantasize more frequently, and have more intercourse partners than erotophobic individuals (Fisher et al, 1988b). Erotophilic people are also more likely to engage in sex-related health care and to use contraception (Fisher et al, 1988b;Herbenick, Reece, & Hollub, 2009;Labranche, Helweg-Larsen, Byrd, & Choquette, 1997;Rudolph, 2016).…”
Section: Erotophobia-erotophiliamentioning
confidence: 99%
“…At least in the context of Study 2, the default cognition in approaching BSEs appeared to be that of human uniqueness, for this condition did not differ from a no-essay control. However, there may be aspects of health settings that can activate concerns about creatureliness (e.g., looking at one's naked figure in the bathroom mirror, seeing one's X-ray in the doctor's office) or aspects of instructional brochures that can make creatureliness more accessible, such as explicit photos (found to deter BSEs among individuals high in erotophobia, Labranche, Helweg-Larsen, Byrd, Choquette, 1997). Applied health workers only stand to gain by considering whether interventions and instructional materials can be delivered in ways that reduce the likelihood of casting BSEs in a creaturely light.…”
Section: Applications For Breast Exam Promotionmentioning
confidence: 99%
“…Engagement in safer sexual behaviors is further found to be an important correlate of higher levels of erotophilia (Fisher, 1984;Fisher, 1990). Other related lines of research have also found correlations between attitudes towards women's genitals and erotophilia, as well as breast selfexamination and erotophilia (Hebernick, 2007;Labranche, et al, 1997).…”
Section: Practical Significance and Correlates Of The Sosmentioning
confidence: 96%